'Responding to a Challenge: Greece's New Policy Towards Israel' - EKAVI ATHANASSOPOULOU (Journal of Southeast European and Black Sea Studies, 2002)
In response to the Israeli-Turkish strategic partnership of the 1990s Greece was driven closer than ever before to Israel. By the end of the 1990s it was clear that Athens had reached a turning point in its policy towards Israel. The PASOK government wished to maintain Greece's traditionally good relations with the Arabs. Nevertheless, it was ready to risk upsetting them in the pursuit of a good relationship with Israel. The promotion of relations with Jerusalem (underdeveloped for over 40 years), was understood to serve national policy goals. It was viewed as part of Greece's strategy towards Turkey (Greece's perennial adversary), as well as of its policy of full alignment with the US and its EU partners. Developments in the regional environment and the ability of the Greek government to respond to opportunities will determine whether Greek-Israeli relations could grow in substance.